Karakteristik Kehilangan Energi dan Potensi Tekanan pada Jaringan Irigasi Perforasi - Negara, I Dewa Gede Jaya; Saadi, Yusron; Supriyadi, Anid; Saidah, Humairo; Kusuma, Lalu Dea Maulana Diendy (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2025)
The magnitude of energy loss in a piping network significantly affects the flow rate that the network can produce. Furthermore, it is important to understand the effect of changes in energy loss and pressure due to changes in the head of the water source. This allows the characteristics of these changes and their impact on the resulting flow rate and discharge to be used as important information in irrigation network design. This test aims to determine the characteristics of the secondary energy loss and residual pressure generated by a perforated irrigation network that uses three secondary network pipes as perforations. The irrigation test was conducted at four head variations: 3.5 m, 3.6 m, 3.7 m, and 3.8 m. The energy loss analysis used the Bernoulli equation, and major and minor energy losses were analyzed at each head variation, including the amount of available water pressure utilized to flow water through the perforated pipe holes. The analysis results showed that a 1 m increase in primary pipe length resulted in an increase in network energy loss of 0.02 m, and each 0.1 m increase in head from 3.5 m resulted in an increase in total energy loss of 0.01 m. At L1  a head of 3.5 m, the pressure is 2.12 m, and at a head of 3.8 m, the pressure is 2.36 m. At L2, the pressure head ranges from 1.97 m to 2.21 m, while at L3, the pressure head ranges from 1.84 m to 2.07 m. Therefore, every 0.1 m increase in head increases the pressure head by 0.08 m in the perforated irrigation network.